2020
DOI: 10.1364/ol.400614
|View full text |Cite
|
Sign up to set email alerts
|

TDLAS-based photofragmentation spectroscopy for detection of K and KOH in flames under optically thick conditions

Abstract: Photofragmentation spectroscopy is combined with tunable diode laser absorption spectroscopy to measure the line shape of the fragment species. This provides flexibility in choosing the UV pulse location within the line shape and accurate quantification of both target species and background fragment concentrations, even under optically thick conditions. The technique is demonstrated by detection of potassium hydroxide (KOH) and atomic potassium K(g) above solid KOH converted in a premixed methane-air flat flam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The main K species released to gas-phase during thermochemical biomass conversion are atomic K, potassium hydroxide (KOH) and potassium chloride (KCl) [8,9]. Usually, KOH dominates in combustion, due to the high oxygen availability, while under fuel-rich conditions, the atomic K concentration can be of the same order of magnitude as, or even exceed, the levels of KOH and KCl [10]. An efficient way to improve the understanding of fuel conversion is to perform well-controlled studies of volatile release from biomass particles combusted in laboratory reactors [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main K species released to gas-phase during thermochemical biomass conversion are atomic K, potassium hydroxide (KOH) and potassium chloride (KCl) [8,9]. Usually, KOH dominates in combustion, due to the high oxygen availability, while under fuel-rich conditions, the atomic K concentration can be of the same order of magnitude as, or even exceed, the levels of KOH and KCl [10]. An efficient way to improve the understanding of fuel conversion is to perform well-controlled studies of volatile release from biomass particles combusted in laboratory reactors [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Selective and quantitative in situ detection of all three main K species in hightemperature reacting flows requires relatively complex optical techniques [10,[19][20][21]. However, gaseous atomic K, here referred to as K(g), provides a good indication of K release, especially during the devolatilization phase, and can be detected in a wide dynamic range and with high time-resolution using tunable diode laser-absorption spectroscopy (TDLAS) [10,16,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…10 Thorin et al used this method to achieve a large dynamic range of K and KOH absolute concentration measurement in the flame. 11 These indicate that the application of absorption saturation incomplete spectroscopy has great potential in extending spectrum gas sensing to a higher concentration range. The work of Rotondaro et al shown that the concentration of rubidium atoms under optically thick conditions can be determined by the absorption peaks reconstructed from the line-shape wings.…”
Section: Introductionmentioning
confidence: 99%
“…Qu et al proposed a method of fitting absorption saturation spectra with simulated spectra, which realized the measurement of absorption saturation incomplete spectra of potassium atoms under optically thick conditions 10 . Thorin et al used this method to achieve a large dynamic range of K and KOH absolute concentration measurement in the flame 11 . These indicate that the application of absorption saturation incomplete spectroscopy has great potential in extending spectrum gas sensing to a higher concentration range.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, tunable diode laser spectroscopy (TDLAS) attracts attention all over the world for gas detections in industrial production and environmental protections [1]- [3]. In the field of gas thermometry, compared with other traditional methods, e.g.…”
Section: Introductionmentioning
confidence: 99%